Comparison of Effectiveness Between Opioid-Free Anesthesia and Opioid-Based Anesthesia on Postoperative Recovery - Mayang Indah Lestari; Emma Novita; Dewi Ainur Rohmah (Indonesian Journal of Anesthesiology and Reanimation, 2026)
Introduction: Opioid-Based Anesthesia (OBA) is a common standard; it carries risks like post-operative nausea and vomiting (PONV) and respiratory issues. Opioid-Free Anesthesia (OFA) offers an alternative that may improve recovery quality, but its efficacy relative to OBA requires more evidence. Objective: This systematic review aims to compare the effectiveness between OFA and OBA on post anesthesia recovery outcomes. Methods: This systematic review followed the PRISMA 2020. Article searches were conducted via PubMed, ScienceDirect, SpringerLink, and Wiley using appropriate keywords. Five randomized controlled trials meeting the inclusion criteria were analyzed and assessed for risk of bias using the Cochrane RoB 2 tool. Results: OFA significantly reduced the incidence of PONV across all studies. OFA also demonstrated equivalent or better analgesia quality in the early postoperative period with lower rescue opioid consumption and showed good hemodynamic stability. However, no significant difference was found in the duration of surgery between the two groups. Conclusion: OFA shows potential as a superior anesthetic strategy compared to OBA in aspects of postoperative recovery, particularly in reducing PONV and additional opioid consumption without compromising analgesia quality. The implementation of OFA has the potential to be integrated into Enhanced Recovery After Surgery (ERAS) protocols. Further studies with larger samples and standardized protocols are needed to strengthen these findings.